Clinical manifestations and laboratory findings and mortality rate of kidney transplant recipients infected with COVID-19 - Shokouh Shayanpour; Maryam Sadat Mavalizadeh; Leila Sabetnia; Heshmatolah Shahbazian; Ali Ghorbani; Zahra Mehraban (Society of Diabetic Nephropathy Prevention, 2023)
Introduction: The emergence of a novel coronavirus (COVID-19) in late December 2019 and its rapid global spread has led World Health Organization (WHO) to introduce it as a very dangerous pandemic. People with underlying disease and a history of organ transplantation are at higher risk for COVID-19 disease compared with healthy people. Objectives: In the present study, clinical and laboratory manifestations in the patients with COVID-19 with a history of kidney transplantation has been investigated. Patients and Methods: This study conducted on 103 COVID-19-positive kidney transplant patients as a descriptive epidemiological study. Clinical and laboratory symptoms of hospitalized renal transplanted patients have been assessed. Statistical analysis of the collected data conducted using SPSS (Statistical Package for Social Sciences, version 22). Results: This study consisted of 103 COVID-19 patients with a history of kidney transplant, of which 64 males (62.1%) and 39 females (37.9%) with an average age of 48.5 ± 13.1 years. The most common clinical manifestations were headache (67%) and shortness of breath (66%). Elevated lactate dehydrogenase (LDH) levels, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) has been observed in 100%, 98.1% and 93.2% of patients, respectively. In 12.6% and 41.7% of patients, the degree of lung involvement was above 75% and 50%-75%, respectively. Moreover, 79.6% of patients has been discharged after improved, while 20.4% of patients died. Conclusion: We found, kidney transplantation may increase COVID-19-related mortality when compared to COVID-19-related mortality in the general population.